Translation and cultural adaptation into Brazilian Portuguese of the Finnish diabetes risk score (Findrisc) and reliability assessment - Barim, Estela Maria [UNESP]; McLellan, Kátia Cristina Portero; Ribeiro, Rogério Silicani; de Carvalho, José Antonio Maluf; Lindström, Jaana; Tuomilehto, Jaakko; Corrente, José Eduardo [UNESP]; Murta-Nascimento, Cristiane [UNESP] (FapUNIFESP (SciELO), 2020)
Introduction: The Finnish Diabetes Risk Score (FINDRISC) is a tool that was initially developed to predict the risk of developing type 2 diabetes mellitus in adults. This tool is simple, quick to apply, non-invasive, and low-cost. The aims of this study were to perform a translation and cultural adaptation of the original version of FINDRISC into Brazilian Portuguese and to assess test-retest reliability. Methodology: This work was done following the ISPOR Principles of Good Practice for the Translation and Cultural Adaptation Process for Patient-Reported Outcomes Measures. Once the final Brazilian Portuguese version (FINDRISC-Br) was developed, the reliability assessment was performed using a non-random sample of 83 individuals attending a primary care health center. Each participant was interviewed by trained registered dieticians on two occasions with a mean interval of 14 days. The reliability assessment was performed by analyzing the level of agreement between the test-retest responses of FINDRISC-Br using Cohen’s kappa coefficient and the intraclass correlation coefficient (ICC). Results: The steps of ISPOR guidelines were consecutively followed without major problems. Regarding the reliability assessment, the questionnaire as a whole presented adequate reliability (Cohen’s kappa = 0.82, 95%CI 0.72 – 0.92 and ICC = 0.94, 95%CI 0.91 – 0.96). Conclusion: FINDRISC was translated into Brazilian Portuguese and culturally adapted following standard procedures. FINDRISC-Br has thus become available for use and has potential as a screening tool in different Brazilian settings and applications.
Tradução e adaptação transcultural para o Português Brasileiro do escore Finlandês de risco de diabetes (Findrisc) e avaliação da confiabilidade
Keywords: Brazil; Diabetes mellitus; Reproducibility of results; Screening; Translating